Patterns of gene expression in the sheep heart during the perinatal period revealed by transcriptomic modeling - Richards, Elaine M. (2015)
Septa from sheep hearts at 130 days gestation, term, and 14-day-old lambs were used to model the changes in gene expression patterns during the perinatal period using Agilent 15k ovine microarrays. We used Bioconductor for R to model five major patterns of coexpressed genes. Gene ontology and transcription factor analyses using Webgestalt modeled the biological significances and transcription factors of the gene expression patterns. Modeling indicated a decreased expression of genes associated with anatomical development and differentiation during this period, whereas those associated with increased protein synthesis and growth associated with maturation of the endoplasmic reticulum rose to term but did not further increase from the near term expression. Expression of genes associated with cell responsiveness, for example, immune responses, decreased at term but expression returned by postnatal day 14. Changes in genes related to metabolism showed differential substrate-associated patterns: those related to carbohydrate metabolism rose to term and remained stable thereafter, whereas those associated with fatty acid oxidation facility rose throughout the period. The timing of many of these maturational processes was earlier in relation to birth than in the rodent. The importance of the transcription factors, estrogen-related receptors, and v-myc avian myelocytomatosis viral oncogene homolog was also highlighted in the pattern of gene expression during development of the perinatal sheep heart.